Leveraging AI to enhance quality for Higher Education Institutions (HEIS) - Sebopelo, Phineas (Review of Artificial Intelligence in Education, 2024)
Purpose: This study critically reviews the literature on adopting and using artificial intelligence platforms to enhance quality in Higher Education Institutions (HEIs). Methodology/Design/Approach: The present study follows a critical literature review on technological innovations, particularly Artificial Intelligence (AI) systems for enhancing quality Open and Distance Education Learning (ODeL). A critical review of the literature was conducted on works that explored the current AI applications that institutions are using to improve the quality of their teaching and learning. This was done through bibliometric analysis, which included a search of popular databases for previously published works. Bibliometric, citation network and keyword analysis were utilized to evaluate the literature review. Findings: The review highlights the potential of AI systems that Higher Education Institutions can utilize to enhance the quality of education. The Artificial Intelligence platforms for enhancing quality in ODeL institutions include the use of Intelligent tutors, Automated grading, and feedback systems, ChatGPT, Chatbots, and Virtual campuses. The adoption and use of technological innovation are closely linked to students’ acceptance, affordability, and usability of the learning technologies. Implications: This study’s results provide implications for researchers, Innovation Hubs, and systems developers and users, including teachers and other education stakeholders.